Hydrogen isotopic substitution of solid methylamine through atomic surface reactions at low temperatures: A potential contribution to the D/H ratio of methylamine in molecular clouds. (30th April 2013) - Oba, Yasuhiro; Chigai, Takeshi; Osamura, Yoshihiro; Watanabe, Naoki; Kouchi, Akira
Abstract We experimentally studied hydrogen (H)–deuterium (D) substitution reactions of solid methylamine (CH3NH2) under astrophysically relevant conditions. We also calculated the potential energy surface for the H–D substitution reactions of methylamine isotopologues using quantum chemical methods. Despite the relatively large energy barrier of more than 18 kJ mol−1, CH3NH2 reacted with D atoms to yield deuterated methylamines at 10 K, suggesting that the H–D substitution reaction proceeds through quantum tunneling. Deuterated methylamines reacted with H atoms as well. On the basis of present results, we propose that methylamine has potential for D enrichment through atomic surface reactions on interstellar grains at very low temperatures in molecular clouds. D enrichment would occur in particular in the methyl group of methylamine.